Analysis of Students' Challenges in Micro-Teaching: A Study at English Education Program, PSDKU Aru - Nussy, Wenssy Steva; Hukom, Salmon James; Ahufruan, Nelson (MATAI: International Journal of Language Education, 2025)
This study examines the challenges encountered by sixth-semester students in the Microteaching class within the English Language Education Study Program at PSDKU Aru University. Microteaching, as a crucial component of teacher education, often exposes various difficulties faced by pre-service teachers. Key challenges identified in this study include nervousness, inadequate teaching knowledge, and barriers categorized into five major areas: procedural, psychological, managerial, instructional, and professional. A qualitative descriptive approach was employed to explore these challenges in depth, using questionnaires and interviews as the primary data collection instruments. The data were analyzed based on students' statements, allowing the researchers to capture detailed insights into their experiences. The findings reveal that most students struggle significantly across all five categories, highlighting gaps in both pedagogical skills and teaching confidence. These results provide a clearer understanding of the complexities students face during Microteaching and suggest the need for targeted interventions in teacher education programs. Enhancing instructional support and offering more practical training opportunities are recommended to better prepare students for real classroom settings. Overall, this study contributes valuable knowledge to the field of English teacher education, particularly in the context of EFL (English as a Foreign Language) instruction.